Enhancing a cluster-based TDMA MAC protocol for vehicle-to-vehicle communications / Abubakar Bello Tambawal - Abubakar Bello , Tambawal (2020)
Vehicular Ad hoc Network technology (VANET) is one of the emerging and promising wireless technology, providing support for vehicles to communicate and share resources, (such as safety messages) through vehicle-to-vehicle (V2V) communications. Sequel to that the Time Division Multiple Access (TDMA) MAC protocol using a cluster-based topology has been proposed by the research community. Most of the existing research works focused on the cluster head (CH) election with very few addressing other critical issues, including cluster formation, efficient time slot allocation, and cluster maintenance. These challenges result in an unstable cluster, which could affect the timely delivery of safety applications. In this thesis, a new approach called enhanced cluster-based TDMA MAC (EC-TMAC) protocol was developed to address these challenges. To achieve that, two CHs were proposed to provide strong cluster stability within the clusters; the primary cluster head (PCH) as the main CH and the secondary cluster head (SeCH) to act as a backup to the PCH. Furthermore, a new algorithm was also developed to provide an efficient CH leadership transition from PCH to SeCH when the PCH can no longer continue with the leadership responsibility. A dynamic time slot allocation strategy using a binary tree algorithm has been proposed to prevent vehicles from the adjacent clusters to reserve the same time slot. The proposed EC-TMAC protocol was evaluated through simulation and validated using a statistical analysis tool. The simulation results obtained show a better performance with increased cluster stability, low rate of merging collision and less communication overhead to the system.